An Exploratory Study of Issues Around Irresponsible Lending and Borrowing in the UK Consumer Credit Market - Ndlovu, Tabani (2005)
The study on issues around irresponsible lending and borrowing in the UK consumer credit market raises more questions than answers. This owes to the secretive and competitive nature of the lending market, whose main artillery is information. It is therefore not surprising that lenders were not forthcoming in volunteering information about their operations.